Factors associated with obtaining employment among opioid use disorder patients enrolled in a therapeutic workplace intervention. (1st September 2021) - Holtyn, August F.; Toegel, Forrest; Novak, Matthew D.; Silverman, Kenneth
Highlights: Patient characteristics may predict employment outcomes and help inform treatment. Patients who obtained employment worked more days in a therapeutic workplace. Illicit opioid and cocaine use were associated with worse employment outcomes. Patients who were usually unemployed were less likely to obtain employment. Abstract: Background: Unemployment is a common problem among adults who have substance use disorder that often persists during treatment and recovery. We identified patient characteristics that were associated with obtaining employment among unemployed adults in opioid use disorder treatment. Methods: This analysis used data from participants (N = 91) who were enrolled in a randomized controlled trial evaluating the effectiveness of a therapeutic workplace in promoting drug abstinence and employment. After a 3-month training period (Phase 1), participants were randomly assigned to a study group and could work for 12 months with an employment specialist who assisted participants in obtaining employment (Phase 2). A logistic regression model was used to identify patient characteristics that were associated with obtaining employment. Results: Of the 91 participants, 39 (42.9 %) obtained employment. Compared to participants who did not obtain employment, participants who obtained employment worked more days in the therapeutic workplace during the training period (Phase 1) [OR (95 % CI) = 1.072 (1.015–1.132), p = .014], provided more opiate- and cocaine-negative urine samples while seeking employment [OR (95 % CI) = 1.015 (1.002–1.027), p = .025], and reported not usually being unemployed at study intake [OR (95 % CI) = 0.229 (0.080–0.652), p = .007]. Conclusions: Our analyses suggest that among unemployed adults in opioid use disorder treatment, those with the lowest rates of therapeutic workplace attendance, lowest rates of drug abstinence while seeking employment, and relatively long histories of unemployment are the least likely to obtain employment. These relations are potentially addressable at a practical level, and future research could build on these findings to improve the effectiveness of employment-based interventions.